Idleness in an Imaginary Country. Identity, Alterity and Genre Issues in W. H. Hudson’s Idle Days in Patagonia (1893) - Lencina, Eva (2020)
This paper characterizes some of the central aspects in Idle Days in Patagonia (1893), by Anglo-Argentine naturalist and writer William Henry Hudson. In this work, the author recalls his stay in the Patagonia territory between 1870 and 1871. We aim to examine the work from the perspective of Imagology, and characterizing the subject’s relation con his self-image and the hetero-image that is developed in the text. Due to the relation with space, idleness is conceived as a productive intellectual activity that shapes a representation of the semimystic link with nature. The focus of our interest is the convergence between identity and alterity in the Argentina rural environment of the 19th century: the development of Hudson’s strategies of swindling his Argentine identity in a text written for English readers, along with a search for empathy with the indigenous alterity in absentia. We also aim to discuss the genre statute in a text as ambiguous as Idle Days in Patagonia, which, like its author, escapes classifications. Finally, we briefly compare this work with an unfinished work by Eduardo Holmberg, due to how the stance each author takes in their respective literary fields enlightens the manners of imaginary representation of the Patagonia space.